Prevalence and Correlates of Insomnia and Excessive Sleepiness in Adults with Obstructive Sleep Apnea Symptoms. Issue 2 (April 2014) - Bjorvatn, Bjørn; Pallesen, Ståle; Grønli, Janne; Sivertsen, Børge; Lehmann, Sverre
This study investigated the prevalence and correlates of insomnia and excessive sleepiness in adults presenting symptoms of obstructive sleep apnea (OSA) in the general population. Randomly selected participants ( N = 1, 502; 50.7% men, 49.3% women), ages 40 to 70 yr. ( M = 53.6, SD = 8.5) were interviewed over the telephone. Insomnia and excessive sleepiness (hypersomnia) were assessed with the Bergen Insomnia Scale and the Epworth Sleepiness Scale, respectively. OSA symptoms were identified by self- or spouse reports on snoring, breathing cessations during sleep, and being tired or sleepy. The prevalence of OSA was 6.2%. Among these participants with OSA, 57.6% reported insomnia and 30.1% reported excessive sleepiness. Furthermore, OSA symptoms were associated with self-reported obesity, hypertension, diabetes, and depression, but only in participants with comorbid insomnia or excessive sleepiness.